2023
DOI: 10.3390/toxins15070447
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR Induces and Aggravates Colitis through NLRP3 Inflammasome-Mediated Pyroptosis in Mice

Abstract: Inflammatory bowel disease (IBD) is a chronic, lifelong gastrointestinal disease, characterized by periods of activity and remission. The etiology of IBD is closely related to environmental factors. Previous studies have shown that the cyanotoxin microcystin-LR (MC-LR) causes intestinal damage, even IBD. To explore MC-LR’s effects and potential mechanisms on IBD occurrence and development, we used dextran-sulfate sodium gavage (DSS) and MC-LR together for the first time in mice. There were four groups of mice:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The prevalence and persistence of CyanoHABs are increasing globally, raising the likelihood that more people will be at risk for cyanotoxin exposure and illness. Additionally, work from our lab has shown that several common comorbidities affecting the liver (nonalcoholic fatty liver disease, or NAFLD) [26][27][28][29], gut (colitis/irritable bowel disease or IBD) [30,31], and airways (asthma) [14] may increase susceptibility to cyanotoxins such as microcystin. These conditions are notable as they are already increasingly common As the incidence and prevalence of diseases such as non-alcoholic fatty liver disease, inflammatory bowel disease, and asthma increase, this may have profound impacts on the health of at-risk populations who are exposed to CyanoHABs.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and persistence of CyanoHABs are increasing globally, raising the likelihood that more people will be at risk for cyanotoxin exposure and illness. Additionally, work from our lab has shown that several common comorbidities affecting the liver (nonalcoholic fatty liver disease, or NAFLD) [26][27][28][29], gut (colitis/irritable bowel disease or IBD) [30,31], and airways (asthma) [14] may increase susceptibility to cyanotoxins such as microcystin. These conditions are notable as they are already increasingly common As the incidence and prevalence of diseases such as non-alcoholic fatty liver disease, inflammatory bowel disease, and asthma increase, this may have profound impacts on the health of at-risk populations who are exposed to CyanoHABs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our previous work identified MC-LR as an independent factor in inducing intestinal damage in vitro and acute toxic animal models. 25,26 In addition, our recent study showed that MC-LR regulates the release of inflammatory factors and fibrosis markers through the CSF1R/ Rap1b signaling pathway in a mouse model, leading to chronic colorectal inflammation, fibrosis, and barrier disruption. The intestinal flora of mice exposed to MC-LR was altered, with an increase in Turicibacter and Clostridium and a decrease in Ruminococcus and Alloprevotella.…”
Section: Introductionmentioning
confidence: 99%